2002
DOI: 10.1177/019251302237296
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Marriage and Psychological Well-being

Abstract: This study examined the relationship between marriage and psychological well-being using a sample from the National Survey of Families and Households panel data. Eight different marital status groups were identified and used to test two competing perspectives explaining the relationship between marriage and individual psychological well-being (protection vs. selection). Findings confirmed the strong effects of marital status on psychological well-being, supporting the protection perspective. The effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
245
6
24

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(293 citation statements)
references
References 30 publications
18
245
6
24
Order By: Relevance
“…Our results also support findings of a systematic review that indicated that increasing use of alcohol increases risk of depression Other findings within our results are also consistent with theory and with existing mental health evidence, adding to the convergent and theoretical validity of our results (Dave & Saffer, 2008;Dolan, Peasgood, & White, 2008). These include women generally reporting worse mental health than men (Cockerham, et al, 2006;Gold, 1998;Patel, Araya, de Lima, Ludermir, & Todd, 1999;WHO, 2000), marriage being protective of mental health (Kim & McKenry, 2002;Mentzakis, McNamee, Ryan, & Sutton, 2012), higher absolute and relative income supporting good mental health (Clark & Oswald, 1996;Lund, et al, 2010;Mentzakis & Moro, 2009), and a strong positive link between better physical and mental health (Clark & Oswald, 2002;Mentzakis, 2011) (although potential adaptation effects cannot be controlled for in our cross-sectional design (Groot, 2000;Heyink, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Our results also support findings of a systematic review that indicated that increasing use of alcohol increases risk of depression Other findings within our results are also consistent with theory and with existing mental health evidence, adding to the convergent and theoretical validity of our results (Dave & Saffer, 2008;Dolan, Peasgood, & White, 2008). These include women generally reporting worse mental health than men (Cockerham, et al, 2006;Gold, 1998;Patel, Araya, de Lima, Ludermir, & Todd, 1999;WHO, 2000), marriage being protective of mental health (Kim & McKenry, 2002;Mentzakis, McNamee, Ryan, & Sutton, 2012), higher absolute and relative income supporting good mental health (Clark & Oswald, 1996;Lund, et al, 2010;Mentzakis & Moro, 2009), and a strong positive link between better physical and mental health (Clark & Oswald, 2002;Mentzakis, 2011) (although potential adaptation effects cannot be controlled for in our cross-sectional design (Groot, 2000;Heyink, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…This conflicts with the literature that has generally found that being married has a unique protective effect on individuals through the regulation of risky behaviours and cautionary attitudes towards potential dangers (Kim & McKenry, 2002;Simon, 2002;Umberson, 1992). It may, however, be the case that the processes governing safe water, specifically, are different than other health-related issues.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 75%
“…The state of being married, relative to individuals who are single, widowed, separated, or divorced, has been found to have a protective effect on individuals, for a number of reasons, including economic efficiency, orderliness, regulation of risky behaviours, and emotional social support (Kim & McKenry, 2002;Simon, 2002;Umberson, 1992). It would, therefore, be expected that a skeptical and more cautionary attitude towards safe drinking water in the home would be observed by married respondents.…”
Section: Variables and Hypothesesmentioning
confidence: 99%
“…An early meta-analysis (Haring, Stock, & Okun, 1984) found that males tend to report better well-being, while longitudinal studies also concluded that marriage supported psychological well-being (Kim & McKenry, 2002;Mentzakis, McNamee, Ryan, & Sutton, 2011). Similarly, increased well-being is commonly associated with higher absolute and relative income (Clark & Oswald, 1996;Mentzakis & Moro, 2009;Oswald, 1997), although consistent indicators for the latter are hard to identify.…”
Section: Discussionmentioning
confidence: 99%